2017
DOI: 10.1136/archdischild-2017-313337
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of pain over time among children with juvenile idiopathic arthritis

Abstract: ObjectivesPain is a very common symptom of juvenile idiopathic arthritis (JIA). Disease activity alone cannot explain symptoms of pain in all children, suggesting other factors may be relevant. The objectives of this study were to describe the different patterns of pain experienced over time in children with JIA and to identify predictors of which children are likely to experience ongoing pain.MethodsThis study used longitudinal-data from patients (aged 1–16 years) with new-onset JIA. Baseline and up to 5-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 38 publications
6
39
1
Order By: Relevance
“…In a multinational quality‐of‐life study from the Pediatric Rheumatology International Trials Organization, pain was found to be a predictor of psychosocial well‐being . In agreement with our study, previous studies have shown that pain at presentation was a strong predictor of persistent pain . In accordance with our results, pain as a predictor of functional disability was also found in a small cross‐sectional study from the US .…”
Section: Discussionsupporting
confidence: 92%
“…In a multinational quality‐of‐life study from the Pediatric Rheumatology International Trials Organization, pain was found to be a predictor of psychosocial well‐being . In agreement with our study, previous studies have shown that pain at presentation was a strong predictor of persistent pain . In accordance with our results, pain as a predictor of functional disability was also found in a small cross‐sectional study from the US .…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, Giancane et al [ 28 ] stated that the pain should be considered as a direct cause and main indication for treatment in JIA patients. Older age at diagnosis and longer disease duration are the risk factors of lower efficacy in reduction of patients' symptoms [ 29 ]. Measuring the JADAS value on the day of the check-up visit may not be the most informative indicator of patients' well-being between the assessments, which may have influenced the evaluation of the relation between S100A12 and disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…The disease course can be unpredictable, and children commonly experience both physical (eg, pain, fatigue, stiffness) and emotional (eg, stress, anxiety, depression) symptoms that may restrict day-to-day function [ 2 - 7 ]. Persistent pain is common and can contribute to adverse psychological effects and functional disability [ 8 , 9 ]. As children mature, they are expected to assume increasing responsibility for disease self-management concomitant with their growing independence and autonomy.…”
Section: Introductionmentioning
confidence: 99%